Cerebral alterations in West African HIV and non-HIV adults aged ≥50: An MRI study. (February 2021) - Bernard, C.; Dilharreguy, B.; Font, H.; Diop, A. Ndoye; Tine, J.M.; Diakhate, I. Cissé; Seydi, M.; Dartigues, J.F.; Dabis, F.; Catheline, G.; Bonnet, F.
Highlights: Atrophy and White Matter Hyperintensities were prevalent in Senegalese people aged ≥50. No clear HIV impact was observed. The role of comorbidities, such as hypertension, was highlighted. Brain MRI studies are encouraged in this population living in West Africa. Abstract: Objectives: To cross-sectionally describe brain alterations in PLHIV aged above 50 years old, receiving antiretroviral treatment (ART) and living in Senegal compared to HIV-negative subjects. Methods: Twenty PLHIV and 26 HIV-negative subjects with comparable socio-demographic and clinical characteristics underwent an MRI exam (3D-T1 and FLAIR sequences). Global atrophy and White Matter Hyperintensities (WMH) were evaluated. After assessing the feasibility and acceptability of MRI scans in this population, we described atrophy and WHM prevalence and associated factors using logistic regressions. Results: Overall, 43.5% of the study sample were aged ≥60 years, 58.7% were women, and 28.3% had hypertension. The overall prevalence of atrophy and WMH was 19.6% [95% CI: 8.1–31.1] and 30.4% [95% CI: 17.1–43.7]. HIV status had no significant effect on atrophy or WMH. Unemployment and hypertension were significantly associated with atrophy, whereas women were less likely to present atrophy. Aged ≥60 years was the only factor associated with WMH. Conclusions: A high prevalence of atrophy and WMH was observed in West African adults aged over 50 years without a clear HIV impact. As brain MRI studies are critical to better understand cognitive and emotional outcomes, we encourage those studies in older PLHIV in West Africa.